Big data shocks an introduction to big data for librarians and information professionals - Weiss, Andrew, 1971- (LITA guides., 2018)
"Big Data Shocks examines the roots of big data, the current climate and rising stars in this world. The book explores the issues raised by big data and discusses theoretical as well as practical approaches to managing information whose scope exists beyond the human scale"--